Surface characterization of lipid biomimetic systems - Disalvo, Edgardo Anibal (2021)
Zeta potential and dipole potential measures are direct operational methodologies to determine the adsorption, insertion and penetration of ions, amphipathic and neutral compounds into the membranes of cells and model systems. From these results, the contribution of charged and dipole groups can be deduced. However, although each method may give apparent affinity or binding constants, care should be taken to interpret them in terms of physical meaning because they are not independent properties. On the base of a recent model in which the lipid bilayer is considered as composed by two interphase regions at each side of the hydrocarbon core, this review describes how dipole potential and zeta potential are correlated due to water reorganization. From this analysis, considering that in a cell the interphase region the membrane extends to the cell interior or overlaps with the interphase region of another supramolecular structure, the correlation of dipole and electrostatic forces can be taken as responsible of the propagation of perturbations between membrane and cytoplasm and vice versa. Thus, this picture gives the membrane a responsive character in addition to that of a selective permeability barrier when integrated to a complex system.